High-frequency oscillatory ventilation attenuates oxidative lung injury in a rabbit model of acute lung injury - Ronchi, Carlos Fernando [UNESP]; Ferreira, Ana Lúcia dos Anjos [UNESP]; Campos, Fabio Joly [UNESP]; Kurokawa, Cilmery Suemi [UNESP]; Carpi, Mario Ferreira [UNESP]; de Moraes, Marcos Aurelio [UNESP]; Bonatto, Rossano César [UNESP]; Faveri, Julio de [UNESP]; Yeum, Kyung-Jin; Fioretto, José Roberto [UNESP] (Royal Soc Medicine Press Ltd, 2011)
Mechanical ventilation (MV) can induce lung oxidative stress, which plays an important role in pulmonary injury. This study compared protective conventional mechanical ventilation (CMV) and high-frequency oscillatory ventilation (HFOV) for oxygenation, oxidative stress, inflammatory and histopathological lung injury in a rabbit model of acute lung injury (ALI). Rabbits (n = 30) were ventilated at FiO(2) 1.0. Lung injury was induced by tracheal saline infusion (30 mL/kg, 38 degrees C). Animals were randomly assigned to: (a) sham control (CG: tidal volume [V(T)] 6 mL/kg, positive end expiratory pressure [PEEP] 5 cmH(2)O, respiratory rate [RR] 40 ipm); (b) ALI + CMV (CMVG: V(T) 6 mL/kg, PEEP 10 cmH(2)O, RR 40 ipm); or (c) ALI + HFOV (HFG: mean airway pressure [Paw] 14 cmH(2)O, RR 10 Hz) groups. Lung oxidative stress was assessed by total antioxidant performance assay, inflammatory response by the number of polymorphonuclear leukocytes/bronchoalveolar lavage fluid/lung and pulmonary histological damage was quantified by a score. Ventilatory and hemodynamic parameters were recorded every 30 min. Both ALI groups showed worse oxygenation after lung injury induction. After four hours of ventilation, HFG showed better oxygenation (partial pressure of oxygen [PaO(2)] - CG: 465.9 +/- 30.5 = HFG: 399.1 +/- 98.2 > CMVG: 232.7 +/- 104 mmHg, P < 0.05) and inflammatory responses (CMVG: 4.27 +/- 1.50 > HFG: 0.33 +/- 0.20 = CG: 0.16 +/- 0.15; polymorphonuclear cells/bronchoalveolar lavage fluid/lung, P < 0.05), less histopathological injury score (CMVG: 5 [1-16] > HFG: 1 [0-5] > CG: 0 [0-3]; P < 0.05), and lower lung oxidative stress than CMVG (CG: 59.4 +/- 4.52 = HFG: 69.0 +/- 4.99 > CMVG: 47.6 +/- 2.58% protection/g protein, P < 0.05). This study showed that HFOV had an important protective role in ALI. It improved oxygenation, reduced inflammatory process and histopathological damage, and attenuated oxidative lung injury compared with protective CMV under these experimental conditions considering the study limitations.
Keywords: high-frequency oscillatory ventilation; conventional mechanical ventilation; acute lung injury; oxidative stress; antioxidants